r Minus g - Robert J. Barro (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Long-term data show that the dynamic efficiency condition r>g holds when g is represented by the average growth rate of real GDP if r is the average real rate of return on equity, E(re), but not if r is the risk-free rate, rf. This pattern accords with a simple disaster-risk model calibrated to fit observed equity premia. If Ponzi (chain-letter) finance by private agents and the government are precluded, the equilibrium can feature rf≤E(g), a result that does not signal dynamic inefficiency. In contrast, E(re)>E(g) is required for dynamic efficiency, implied by the model, and consistent with the data. The model satisfies Ricardian Equivalence because, without Ponzi finance by the government, a rise in safe assets from increased public debt is matched by an increase in the safe (that is, certain) present value of liabilities associated with net taxes.
Keywords: 330